Prevalence of De Quervain disease in infant caregivers and its association with risk factors - Manzoor, Aneeqa; Syed, Sidra; Nadeem, Mishal; Khawar Butt, Sara; Zafar, Syeda Nabiha; Hanif, Muhammad Kamran (Journal of the Pakistan Medical Association, 2024)
De Quervain’s disease (DQD) is commonly reported in mothers during pregnancy up to delayed postpartum period. A cross-sectional study was conducted to assess infant caregivers who visited the paediatric outpatient department or vaccination centre in two hospitals of Lahore, during the months of May and June, 2021. A total of 190 subjects were interviewed directly and assessed by applying Finkelstein’s test on both hands. Data was collected using Numeric Pain Rating Scale (NPRS) and Patient Rated Wrist Evaluation (PRWE) from positive subjects. They were asked to report their pain and difficulty level of the affected hand with worsened symptoms. The results exhibited 26.8% prevalence of DQD in a sample size of 190. Infant’s age, lifting frequency and hand dominance were proved significant risk factors. However, caregiver’s age, history of wrist pain, infant weight and relationship with infant were proved insignificant. Mean PRWE pain and functional scores were 23.14 ± 7.72 and 18.53 ± 6.09, respectively. Keywords: De Quervain disease; infant; caregivers; prevalence; risk factors.